VARIASI LINGUISTIK BAHASA TETUN DIALEK FEHAN: SEBUAH KAJIAN AWAL - Adnyana, I Ketut Suar (Linguistik Indonesia, 2018)
This qualitative research focused on the linguistic variations of the matrilineal society of Tetun ethnic background in Belu, East Nusa Tenggara. The purpose of this study is to describe differences in the use of prosodic features, lexicons, and imperative sentences between men and women. The informants were determined by using a snowball sampling technique. Data were collected by means of nonparticipatory method through recording technique and interviews. The result of this study indicates that there are differences in the linguistic variations between men and women. In terms of prosodic features, women tend to lengthen a vowel sound at the end of a word. In the lexicon level, the word he’e ‘yes’ is used by men and women in formal and informal situation whereas hi’i ‘yes’ is used only by women in informal situation. In addition, there is a difference in the use of address terms. Women use mane and bo’o for boys while men use bete and bu’i for girls in addressing their children. In the syntactic level, men use more varied types of imperative sentences. The data show that although women occupy a superordinate position in the society, they tend to use more polite imperative utterances.